PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING DALAM MENINGKATKAN HASIL BELAJAR IPA SISWA SEKOLAH DASAR - Eva Wati; Siti Sahronih (Institut Pendidikan dan Bahasa Invada, 2022)
Science is one of the important subjects in elementary schools that must be learned by students. This study aims to describe the implementation of the project based learning model in science learning in grade IV elementary school. This research is a qualitative research, with a descriptive research approach.This study aims to improve Science Learning Outcomes. The learning model of Project Based Learning on the learning outcomes of elementary school students. This research method will help students in understanding to improve student learning outcomes. The samples involved in this study were fourth grade students at SDN 3 Mundu, totaling 36 students. This data collection was carried out using the test method with this test instrument consisting of learning outcomes in the form of multiple choice questions to measure student learning outcomes and observations with instruments in the form of observation sheets to measure student activity in the learning process.Data analysis in this study used descriptive analysis. The results showed that learning with the Project Based Learning learning model could improve student learning outcomes with an average score of 74.6 and 78.75 with classical completeness of 65% and 90%. The percentage increase in student learning outcomes classically from cycle I to cycle II is 25%. These results lend credence to the idea that student learning outcomes are enhanced by learning experiences.